MOF-derived ZnCo2O4 porous micro-rice with enhanced electro-catalytic activity for the oxygen evolution reaction and glucose oxidation. Issue 15 (2nd March 2020) - Zhang, Daojun; Wang, Zimo; Li, Jiakai; Hu, Chengming; Zhang, Xiaobei; Jiang, Bei; Cao, Zhi; Zhang, Jingchao; Zhang, Renchun
Abstract : A porous ZnCo2 O4 micro-rice like microstructure was synthesized via calcination of a Zn–Co MOF precursor at an appropriate temperature. Abstract : A porous ZnCo2 O4 micro-rice like microstructure was synthesized via calcination of a Zn–Co MOF precursor at an appropriate temperature. The as-prepared ZnCo2 O4 sample presented good electrocatalytic oxygen evolution reaction performance with a small overpotential ( η 10 = 389 mV) and high stability in basic electrolyte. Furthermore, in basic medium, the as-synthesized ZnCo2 O4 micro-rice also showed good electrocatalytic activity for glucose oxidation. A ZnCo2 O4 micro-rice modified glass carbon electrode may be used as a potential non-enzymatic glucose sensor. The excellent electrocatalytic OER and glucose oxidation performances of ZnCo2 O4 might be attributed to the unique porous structure formed by the nanoparticles. The porous architecture of the micro-rice can provide a large number of electrocatalytically active sites and high electrochemical surface area (ECSA). The result may offer a new way to prepare low-cost and high performance oxygen evolution reaction and glucose oxidation electrocatalysts.